2001
DOI: 10.1159/000048128
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Therapy in the Glucocorticosteroid-Dependent Child: Metabolic and Linear Growth Effects

Abstract: Pharmacological doses of glucocorticosteroids given chronically are associated with a variety of negative side effects which impact the prolonged use of these potent anti-inflammatory agents. They have catabolic effects on protein, resulting in poor tissue healing, an increased incidence of infections and accelerated bone loss. Insulin resistance to both hepatic and peripheral tissues is a common consequence of chronic steroid use, leading at times to impaired carbohydrate metabolism. Steroids affect both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…These drugs, with nonspecific actions, possess numerous side effects, and their chronic use must be used with caution in patients (36,37). In our study, prednisolone pretreatment was effective at reducing the majority of parameters measured, consistent with previous findings (38 -40), although treated rats lost considerable body weight attributed to catabolism, a major side effect with steroid therapy (41,42). Although steroids are widely used in colitis therapy, it is of interest that rats treated with steroid 24 h after the induction of colitis showed no appreciable therapeutic effects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These drugs, with nonspecific actions, possess numerous side effects, and their chronic use must be used with caution in patients (36,37). In our study, prednisolone pretreatment was effective at reducing the majority of parameters measured, consistent with previous findings (38 -40), although treated rats lost considerable body weight attributed to catabolism, a major side effect with steroid therapy (41,42). Although steroids are widely used in colitis therapy, it is of interest that rats treated with steroid 24 h after the induction of colitis showed no appreciable therapeutic effects.…”
Section: Discussionsupporting
confidence: 92%
“…This may be explained by the delayed time it takes for steroids to become effective, which may have been too late for any appreciable activity of prednisolone on disease pathology. Alternatively, steroid treatments tend to inhibit natural healing processes associated with disease pathology (41,43).…”
Section: Discussionmentioning
confidence: 99%
“…GH is one of the most important factors that regulates postnatal longitudinal growth, body weight, and body composition in mammals (18,(41)(42)(43)(44)(45). GH exerts anabolic actions in skeletal muscle by both promoting muscle development and facilitating nutrient uptake and utilization in the muscle, thereby coordinating global energy expenditure and body composition (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…GH treatment on the GCs-induced osteopenia may increase bone formation and bone mass or density, with a wide range of therapeutic dose (0.1 U/day to 0.5 U/day or more) and duration (1 week to 3 months) Eriksen et al 1993;Slootweg 1993;Vandeweghe et al 1993;Inzucchi and Robbins 1994;Ørtoft et al 1999). Several studies have shown that GH improved the body composition, bone metabolism, and linear growth in the GCs-dependent children (Mauras 2001(Mauras , 2002. Therefore GH has been expected to prevent, treat, or even facilitate the recovery of the GCs-induced osteopenia.…”
Section: Discussionmentioning
confidence: 99%